A Methodology for Sea Border Intrusion Alert and Black Box System Using IOT - Jayaselvi, P; Periasamy, J K; Padma Priya, M; Samundeswari, S (International Journal of Psychosocial Rehabilitation, 2019)
We have heard many incidents of fishermen shot in maritime boundary which have enraged the citizens of the state. The technology is increasing at a faster pace in various sectors. Security based technological advancement are utilized by us in our day-to-day life. In marine services, knowingly or unknowingly our fishermen find it difficult to locate the border zone. So they are getting captured by the other countries and been arrested. So in order to overcome this issue and provide alert for the fishermen, we propose this system to provide an alert. The system consists of a border alerting section with a microcontroller which provides an alert while nearing the border and helps the boat to go in the reverse direction. The navy is also intimidated with the location of the boat that is displayed on the system using latitude and longitude coordinates. We also make use of a voice IC to utilize it as a black box in critical situations.